Institutional change and the quality of palm oil: an analysis of the artisanal processing sector in Ghana - Osei-Amponsah, C.; Stomph, T.-J.; Visser, L.; Sakyi-Dawson, O.; Adjei-Nsiah, S.; Struik, P.C. (International Journal of Agricultural Sustainability, 2014)
In Ghana, most oil palm fruits are produced by smallholders and processed by female artisanal processors. However, the ensuing crude palm oil (CPO) is high in free fatty acids and therefore cannot be sold in remunerative local or export markets. An earlier diagnostic study indicated that two main factors cause the poor quality: the processing practice of leaving harvested fruits unprocessed for up to 21 days and the use of lorry tyres as fuel to cook the fruits. Furthermore, the tyre-burning practice affects the health of people working and living around the processing facilities. This study describes the effect of action research undertaken with processors and the creation of a stakeholder platform in which Chiefs, the District Assembly, and a Concertation and Innovation Group collaborated to address the issues. The emerging institutional changes are assessed against baseline information. Awareness was raised about the dangers of tyre-burning, and CPO quality was improved by establishing the optimal time to leave fruits before processing. However, the prevailing market circumstances led producers to opt to produce greater quantities of oil rather than better-quality oil. © 2014 © 2014 Taylor & Francis.
Keywords: Ghana; innovations; institutional entrepreneur; interactions; Kwaebibirem District; stakeholders' platform